2006
DOI: 10.1155/mi/2006/54632
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salivary Interleukin 2 and Interleukin 6 in Patients With Burning Mouth Syndrome

Abstract: The etiology of BMS remains unknown. Role of various cytokines has been implicated in the development of BMS. The aim of this study was to evaluate levels of salivary IL-2 and IL-6 in patients with BMS, compared with age-matched healthy volunteers (control group). Whole saliva from 30 patients with BMS, age range 55–65, was tested for the presence of IL-6 and IL-2 by enzyme immunoassay. Control group consisted of 30 healthy participants, aged 55–65 years. Saliva IL-2 concentrations in BMS were significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 9 publications
5
89
5
3
Order By: Relevance
“…Some studies have revealed changes in the composition of the saliva of BMS patients, including an increase in sodium, total protein, albumin, immunoglobulin (Ig)A, IgG, IgM, amylase, lysozyme [7], interleukin (IL)-2, IL-6 [8] and neural growth factor (NGF) [9]. These salivary changes are associated with mucosal atrophy and/or subtle inflammation, determining the oral neuropathy, dry mouth and taste alterations in BMS [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed changes in the composition of the saliva of BMS patients, including an increase in sodium, total protein, albumin, immunoglobulin (Ig)A, IgG, IgM, amylase, lysozyme [7], interleukin (IL)-2, IL-6 [8] and neural growth factor (NGF) [9]. These salivary changes are associated with mucosal atrophy and/or subtle inflammation, determining the oral neuropathy, dry mouth and taste alterations in BMS [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, statistically high salivary levels of IL-2 and Il-6 that could be associated with the severity of BMS suggest that these markers indicate the existence of an inflammatory and immunologic mechanism behind its etiology 47 .…”
Section: Saliva Changesmentioning
confidence: 99%
“…El aumento de MUC1 podría resultar de la adaptació n de las cé lulas de la mucosa a la irritació n cró nica constante 20 . Por otra parte, los valores de interleucinas (IL) 2 y 6 de la saliva son elevados en estos pacientes, correlacioná ndose con la gravedad de la enfermedad 23 . Las IL actú an como neuromoduladores o neurotransmisores potenciales en el procesamiento nociceptivo del dolor neuropá tico y de la hiperalgesia.…”
Section: Aspectos Fisiopatológicosunclassified
“…Todos estos há bitos parafuncionales son, a nuestro juicio, la clave principal del SBA. La fricció n repetitiva de diversas zonas de la mucosa oral (lengua, labios) con las estructuras má s duras pró ximas (mucosa masticatoria palatina, dientes, pró tesis) provoca pequeñ os focos inflamatorios (de ahí la alteració n observada de mediadores de la inflamació n como IL-2 y IL-6), que a su vez propician la aparició n de neuropé ptidos (sustancia P, neurocininas) 17,20,23,24 .…”
Section: Claves Diagnósticas Del Sı´ndrome De Boca Ardienteunclassified